Utilization of ethanolamine phosphate phospholyase as a unique astrocytic marker - Tsujioka, Hiroshi; Yamashita, Toshihide (Frontiers in Cellular Neuroscience, 2023)
Astrocytes play diverse roles in the central nervous system in both physiological and pathological conditions. Previous studies have identified many markers of astrocytes to analyze their complicated roles. Recently, closure of the critical period by mature astrocytes has been revealed, and the need for finding mature astrocyte-specific markers has been growing. We previously found that Ethanolamine phosphate phospholyase (Etnppl) was almost not expressed in the developing neonatal spinal cord, and its expression level slightly decreased after pyramidotomy in adult mice, which showed weak axonal sprouting, suggesting that its expression level negatively correlates with axonal elongation. Although the expression of Etnppl in adult astrocytes is known, its utility as an astrocytic marker has not yet been investigated in detail. Here, we showed that Etnppl was selectively expressed in adult astrocytes. Re-analyses using published RNA-sequencing datasets revealed changes in Etnppl expression in spinal cord injury, stroke, or systemic inflammation models. We produced high-quality monoclonal antibodies against ETNPPL and characterized ETNPPL localization in neonatal and adult mice. Expression of ETNPPL was very weak in neonatal mice, except in the ventricular and subventricular zones, and it was heterogeneously expressed in adult mice, with the highest expression in the cerebellum, olfactory bulb, and hypothalamus and the lowest in white matter. Subcellular localization of ETNPPL was dominant in the nuclei with weak expression in the cytosol in the minor population. Using the antibody, adult astrocytes were selectively labeled in the cerebral cortex or spinal cord, and changes in astrocytes were detected in the spinal cord after pyramidotomy. ETNPPL is expressed in a subset of Gjb6+ astrocytes in the spinal cord. The monoclonal antibodies we created, as well as fundamental knowledge characterized in this study, will be valuable resources in the scientific community and will expand our understanding of astrocytes and their complicated responses in many pathological conditions in future analyses.